(untitled) (Journal of Asian Development Studies, 2025)
Rapid urbanization, industrialization and unsustainable consumption and management of resources have increased the environmental problems in the region of South Punjab in Pakistan leading to threats for sustainable development. The study evaluated the level of environmental awareness, the effectiveness of environmental policy implementation and pinpointed the challenges and opportunities for sustainable development. A combination of both qualitative and quantitative research designs was used. Descriptive analysis, Chi-square tests, Principal Component Analysis (PCA) and multiple regression analysis were employed to analyze data. The results indicated that the level of environmental awareness was moderate among 52.0%, high among 29.0% and low among 19.0% of the respondents. Most recognized environmental issues were air pollution (89.5%), water pollution (86.8%) and climate change (81.3%). Environmental awareness was significantly affected by education (χ² = 32.45, p< 0.001) and the regression model accounted for 62.4% of the variance (R² = 0.624), with education being the strongest predictor (β = 0.412). PCA explained 80.8% of the total variance. Water scarcity (Mean = 4.61) was identified as the most pressing environmental issue and tree plantation campaigns (Mean = 3.71) were the activity that was most effective in addressing the environmental issue. The study found that building institutional capacities, effective policy implementation, EE, community involvement and sustainable use of resources are vital in enhancing environmental governance for sustainable development in South Punjab.